2022
DOI: 10.5902/2179769268294
|View full text |Cite
|
Sign up to set email alerts
|

Experiência com mídias sociais para ações em saúde com idosos durante a pandemia Covid-19

Abstract: Objetivo: relatar a experiência de uso de mídias sociais para ações em saúde com idosos durante a pandemia Covid-19. Método: trata-se de um relato de experiência do projeto de extensão intitulado “Vovôs e vovós conectados: ligados na Internet na qualidade de vida”, realizado de abril a dezembro de 2020, mediado por interações síncronas e assíncronas, utilizando ferramentas digitais e discutido à luz da Política do Envelhecimento Ativo e da Década do Envelhecimento Saudável. Resultados: as abordagens virtuais b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
(22 reference statements)
0
3
0
2
Order By: Relevance
“…Other studies have been developed with a focus on social aspects, including biopsychosocial educational activities. Gallo et al (2022) highlighted that the guided use of social media by older adults contributes effectively to the maintenance of social relationships and health promotion from the perspective of healthy aging, even during a health crisis with global repercussions. Oliveira et al (2021) reported that the higher the scores on the life satisfaction scale, the higher the scores on the leisure attitudes scale, which may demonstrate that the elderly with more satisfaction with life have a more positive attitude towards leisure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have been developed with a focus on social aspects, including biopsychosocial educational activities. Gallo et al (2022) highlighted that the guided use of social media by older adults contributes effectively to the maintenance of social relationships and health promotion from the perspective of healthy aging, even during a health crisis with global repercussions. Oliveira et al (2021) reported that the higher the scores on the life satisfaction scale, the higher the scores on the leisure attitudes scale, which may demonstrate that the elderly with more satisfaction with life have a more positive attitude towards leisure.…”
Section: Resultsmentioning
confidence: 99%
“…The literature review took place between January and April 2023, prioritizing publications between 2018(Azevêdo et al, 2022Balaguera & Arberas, 2022;Cruz, Pereira and Raymundo, 2022;Cruz, Pereira, Pizzetti et al, 2022;Damasceno et al, 2018;Fiamoncini et al, 2022;Glasinovic et al, 2022;Gallo et al, 2022;Hernández, 2022;Lucas et al, 2022;Nascimento et al, 2020;Oliveira et al, 2019;Oliveira et al, 2021;Previato et al, 2019;Sá et al, 2022;Souza Júnior, Siqueira et al, 2022;Souza Júnior, Viana et al, 2022;Tedeschi et al, 2022;Veras et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Outros estudos foram desenvolvidos com enfoque nos aspectos sociais incluindo atividades educativas biopsicossocial. Gallo et al (2022) destacaram que o uso orientado de mídias sociais pelos idosos contribui de maneira eficaz para a manutenção das relações sociais e promoção da saúde na perspectiva do envelhecimento saudável, mesmo durante uma crise sanitária de repercussão global.…”
Section: Resultsunclassified
“…. O levantamento bibliográfico ocorreu entre os meses de janeiro a abril de 2023, priorizando as publicações entre 2018 e 2022 (Azevêdo et al, 2022;Balaguera & Arberas, 2022;Cruz, Pereira e Raymundo, 2022;Cruz, Pereira, Pizzetti et al, 2022;Damasceno et al, 2018;Fiamoncini et al, 2022;Glasinovic et al, 2022;Gallo et al, 2022;Hernández, 2022;Lucas et al, 2022;Research, Society andDevelopment, v. 12, n. 6, e13712642152, 2023 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v12i6.42152 3 Nascimento et al, 2020;Oliveira et al, 2019;Oliveira et al, 2021;Previato et al, 2019;Sá et al, 2022;Silva et al, 2022;Souza Júnior, Siqueira et al, 2022;Souza Júnior, Viana et al, 2022;Tedeschi et al, 2022;Veras et al, 2022).…”
Section: Metodologiaunclassified